Fortgeschrittene gastrointestinale Stromatumoren: Welche Rolle spielt die Chirurgie im multimodalen Konzept heute? = Advanced gastrointestinal stromal tumors : What role does surgery currently play in multimodalconcepts? - Ronellenfitsch, Ulrich; Henzler, Thomas; Menge, Franka; Hohenberger, Peter (Der Chirurg, 2016)
Background: Gastrointestinal stromal tumors (GIST) have an incidence of 1-2/100,000 and thus constitute the most common mesenchymal neoplasm of the digestive tract. Their specific tumor biology with mutations in the protooncogenes c-KIT and PDGFR α acting as drivers of tumor growth facilitate targeted therapy with tyrosine kinase inhibitors. In this context, there are several specific indications for surgery in patients with advanced GIST. Objective: This article discusses the importance of surgery within multimodal therapeutic concepts for advanced GIST. Material and methods: The results of a selective literature search including own studies and case reports are presented. Results: For large GIST at unfavorable anatomical locations, which are not amenable to organ-sparing resection, neoadjuvant imatinib therapy is the standard upfront treatment prior to surgery in the case of imatinib-sensitive mutations in the c-KIT protooncogene. This usually reduces the extent of resection without increasing perioperative morbidity. In the metastatic setting, surgery can constitute a significant part of multimodal therapy in patients with a generalized response to drug therapy by resection of residual tumor masses, although there are no prospective studies to prove a beneficial effect on overall survival. In patients with focal progression on anti-proliferative therapy, local therapeutic measures can make an important contribution to multimodal tumor control. In patients with generalized progression, an operation should only be performed in highly selected cases with the goal of symptom control. Local ablative therapies, such as radiofrequency ablation (RFA), irreversible electroporation (IRE) and selective internal radiotherapy (SIRT) are a therapeutic option particularly for liver metastases. Conclusion: Surgery plays an important role in the multimodal therapy of advanced GIST particularly in the neoadjuvant setting. Its role is more limited in metastatic stages where systemic treatment represents the frontline therapeutic approach.
Gesehen am 14.05.2019